Religion, materialism and ecology
1 online resource.
Keywords: "This timely collection of essays by leading international scholars across religious studies and the environmental humanities advances a lively discussion on materialism in its many forms. While there is little agreement on what 'materialism' means, it is evident that there is a resurgence in thinking about matter in more animated and active ways. The volume explores how debates concerning the new materialisms impinge on religious traditions and the extent to which religions, with their material culture and beliefs in the Divine within the material, can make a creative contribution to debates about ecological materialisms. Spanning a broad range of themes, including politics, architecture, hermeneutics, literature, and religion, the book brings together a series of discussions on materialism in the context of diverse methodologies and approaches. The volume investigates a range of issues including space and place, hierarchy and relationality, the relationship between nature and society, human and other agencies, and worldviews and cultural values. Drawing on literary and critical theory, and queer, philosophical, theological and social theoretical approaches, this ground-breaking book will make an important contribution to the environmental humanities. It will be a key read for postgraduate students, researchers and scholars in religious studies, cultural anthropology, literary studies, philosophy and environmental studies"--